The Oxford handbook of deaf studies in language - Marschark, Marc; Spencer, Patricia Elizabeth (Oxford ; New York : Oxford University Press, 2016)
Lit.opg.; reg.
Includes bibliographical references and index.
Keywords: Deaf -- Means of communication; Deaf -- Education; Sign language